Hydrological spectral indicators for Iraq using remote sensing and GIS - Aseel Jassim Mohammed Awash; Prof-Dr. Ayad Ashour AL- Taee; Prof.Dr. Abbas Fadil Abed Al-Gharaghouli (Journal of College of Education, 2024)
The study of hydrological spectral indicators is one of the modern trends in detecting changes in water resources by adopting space visualizations and analyzing spectral fingerprints to detect water. Data from the satellites (Landsat-8-5) and (Sentinel-2B) were relied upon to detect hydrological indicators, including the natural water difference index for the wet and dry season in Iraq and the difference in the spatial distribution of the index categories by classification. The soil moisture difference index was adopted. The index was classified into five categories for the wet and dry season and the spatial change of the index was detected. The plant indicators were adopted, including the derivation of the vegetation difference index (NDVI) for Iraq and the adoption of the period 1980 for the wet and dry season and the year 2022 for the wet and dry season and extracting the changes between the period and adopting the (Marcov) model to predict spatial changes and their relationship to hydrological variables, as well as adopting the biological crust index (Crust Index (CI) and classifying it into five categories for the wet and dry season and detecting the extent of soil deterioration as a result of hydrological changes. The surface particle volume index was also adopted. (GSI) is one of the spectral indicators for calculating the volumes of surface soil particles, i.e. what the soil texture and components represent and their relationship to hydrological variables and their effect on soil texture and their effect on soil moisture and water retention. The Land Degradation Index (LDI) was adopted, which is an index of land cover degradation as a result of the loss of its biological and economic productivity. The land cover was classified for the wet and dry season and the spatial distribution of the difference in degradation of the surface of Iraq was calculated. The land cover (Land Use) and the extent of change in areas as a result of hydrological changes between the wet and dry season were classified. The agricultural drought and water stress index (hydrological desertification) was adopted. It is an index based on determining the location of agricultural lands that are affected by water stress (drought) and determining the spatial variables and calculating the rate of degradation in the land cover of Iraq
Keywords: Geographic Information Systems, Remote Sensing, Satellite Visualizations, Hydrological Indicators, Vegetation Density, Biocrust